Celebridades empreendedoras e narrativas inspiracionais: pacotes biopolíticos de Bel Pesce e Flávio Augusto da Silva (Geração de valor) no âmbito da comunicação e do consumo - Figueiredo, Camila Brandão Simurro (2018)
The present study has as main theme the relations between communication, consumption and entrepreneurial culture, and as object of study the biographical and autobiographical narratives of Brazilian entrepreneurs, in this case, Bel Pesce and Flávio Augusto da Silva, present in its multiple digital media supports. We aim to understand how these agents resignify self-help literature in contemporary times, conceiving what we denominate “entrepreneurial self-help” (CASAQUI, 2017a). On the agenda, there is the maximum recurrence that everyone can, and should, be entrepreneurs regardless of any personal or financial barrier. In this scenario, it was possible to understand that these discourses intend to consolidate “conduct models” (EHRENBERG, 2010) that reinforce the idea of “selfentrepreneurship” and high performance as essential qualities to achieve success. Such discourses present themselves as “recipes”, prescriptions based on “exemplary life histories”, reiterating the logics of justification of the new “spirit of capitalism” (BOLTANSKI; CHIAPELLO, 2009). It is also through the production and circulation of these narratives in the media that these entrepreneurial agents become contemporary celebrities, and it’s the final proof that legitimates their advices. Therefore, we propose a critical view of this phenomenon, in order to understand how the discursivity is constructed in these entrepreneur’s life histories, through the Discourse Analysis theoretical-methodological proposal, based on Foucault’s discursive categories (2008b), related to life course’s analysis proposed by Giele and Elder Jr. (1998). The discourses, in the “foucaultian approach”, are practices that operate in the “leading of conduct”. Regarding the findings of the analyzed discourses, it was possible to perceive the following characteristics: the testimony as a discourse format; the constitution of a biographical space (ARFUCH, 2010); the mission of prescribing conducts and moral profiles through the inspiration (understood as culture and as communicational process); “entrepreneurial self-help” as the main discursive strategy; moral attributes constituent of the entrepreneurial culture as overcoming challenges (daily and business), goals, passion for work, to justify entrepreneurship as the best alternative for the construction of a “better world”, an “entrepreneurial society” (DRUCKER, 2011). In summary, entrepreneurship, as na economic and social conduct, allows the current neoliberal system to include more subjects in their rationalities, processes and, self-blame.